[Columbus Anchor] - (:unkn) unknown (My University, 2010)
Photo of the Columbus Anchor with an inscription placed in front of the Victoria Institute, known today as the National Museum and Art Gallery, Port of Spain, Trinidad and Tobago.
Colour: Black and White; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Antiquities--Trinidad and Tobago; Monuments--Trinidad and Tobago; 1953; Anchors--Trinidad and Tobago; Historic buildings--Trinidad and Tobago